O MINISTÉRIO PÚBLICO E AS POLÍTICAS PÚBLICAS: DEFININDO A AGENDA OU IMPLEMENTANDO AS SOLUÇÕES? - Coelho, Sérgio Reis; Kozicki, Katya (Revista da AJURIS - Qualis A2, 2013)
PUBLIC MINISTRY AND PUBLIC POLICIES: SETTING THE AGENDA AND IMPLEMENTING SOLUTIONS? RESUMO: O artigo investiga qual o papel desempenhado pelo Ministério Público na discussão que envolve políticas públicas, buscando compreender a influência exercida por esta instituição no debate. Afirma-se não ser a instituição ministerial formuladora ou implementadora de políticas, tampouco o Poder Judiciário, pois se compreende o processo de criação de políticas públicas como algo complexo, que envolve tempo e mobilização de equipamentos e recursos públicos alheios tanto à vontade ministerial quanto ao poder jurisdicional. Defende-se que o Ministério Público está envolvido no processo de criação de políticas públicas, mas nas fases iniciais, no que Frey (2000) denomina de fases de percepção e definição de problemas e de agenda setting. PALAVRAS-CHAVE: Ministério Público; políticas públicas; formulação. ABSTRACT: The paper investigates what role is played by Public Ministry in the discussion involving public policies seeking to understand the influence exercised by this institution in this debate. It is stated that unless the ministerial institution being the responsible by the formulation or public policy implementing, not even the judiciary can be due to the fact we understand being the process of creation of public policies as something rather complex, which involves time and mobilization of public resources and equipment unrelated to both the ministry will as well as on the judicial power. It also argues that the Public Ministry is involved in the creation of public policies, but in the early stages, as Frey (2000) calls the stages of perception and problem definition and agenda setting. KEYWORDS: Public Ministry; public policies; formulation. SUMÁRIO: Introdução; 1 Políticas públicas: construção do conceito e evolução; 2 Fases do ciclo das políticas públicas; 3 A Constituição Federal de 1988 e o novo perfil da instituição ministerial; 4 De que forma estabelece-se a relação entre o Ministério Público e a sociedade civil?; 5 Afinal, qual o lugar do Ministério Público dentro do policy cycle? Considerações finais; Referências. SUMMARY: Introduction; 1 Public policies: the concept’s designing and its evolution; 2 Stages of the public policies cycles; 3 The 1988 Federal Constitution and the new profile of the ministerial institution; 4 On what basis is established the link between the Public Ministry and civil society?; 5 After all, what is the Public Ministry role within the policy cycle? Final Regards; References.